2001
DOI: 10.1002/ijc.10346
|View full text |Cite
|
Sign up to set email alerts
|

Lens epithelial cell protection by aminothiol WR-1065 and anetholedithiolethione from ionizing radiation

Abstract: SUMMARY Lens epithelium disorganization, glutathione (GSH) depletion, and epithelial cell death have been incriminated in the cytopathogenic mechanisms that lead to cataract formation following UVB and x-ray exposures. The objective of this study was to determine the in vitro capacity of the aminothiol WR-1065, the active metabolite of amifostine, and anetholedithiolethione (ADT or Sulfarlem ) to protect bovine lens epithelial cells against x-ray irradiation. WR-1065 and ADT were used at a concentration of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Amifostine, an organic thiophosphate prodrug, is clinically used as a cytoprotective adjuvant in cancer chemotherapy due to its free radical scavenging capacity and ability to detoxify reactive drug metabolites [92]. Belkacémi et al (2001) reported that the active metabolite of amifostin, aminothiol WR-1065, protected bovine epithelial cells against X-ray radiation of 10 Gy (2 Gy per minute) as evidenced by the elevation of GSH content, enhanced cell viability, and a decrease in both nuclear condensation and epithelial cell apoptosis [93].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Amifostine, an organic thiophosphate prodrug, is clinically used as a cytoprotective adjuvant in cancer chemotherapy due to its free radical scavenging capacity and ability to detoxify reactive drug metabolites [92]. Belkacémi et al (2001) reported that the active metabolite of amifostin, aminothiol WR-1065, protected bovine epithelial cells against X-ray radiation of 10 Gy (2 Gy per minute) as evidenced by the elevation of GSH content, enhanced cell viability, and a decrease in both nuclear condensation and epithelial cell apoptosis [93].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Free radical scavenging activity has been demonstrated by NAC in multiple cell types [21–23] including fibroblasts [24], as well as in amifostine [25] and in genistein [26]. Evidence also demonstrates that NAC [27], amifostine [28–31], genistein [32–34], and oltipraz [35–39] either serve as precursors or induce the presence of cellular defense enzymes that catalyze the reduction of H 2 O 2 , ·OH, and O 2. Cytoprotection afforded by amifostine includes increased cell viability [28,29,40,41], reduced DNA damage [42–44], and reduced apoptosis [45,46] after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also demonstrates that NAC [27], amifostine [28–31], genistein [32–34], and oltipraz [35–39] either serve as precursors or induce the presence of cellular defense enzymes that catalyze the reduction of H 2 O 2 , ·OH, and O 2. Cytoprotection afforded by amifostine includes increased cell viability [28,29,40,41], reduced DNA damage [42–44], and reduced apoptosis [45,46] after irradiation. As a receptor protein tyrosine kinase inhibitor genistein can play an antioxidant role by ameliorating the effects of ROS signal transduction including reducing apoptosis in H 2 O 2 treated fibroblasts [47,48], reducing vascular damage [49], suppressing cyclooxygenase expression [50], and inhibiting the induction of Stat1 activity [51].…”
Section: Introductionmentioning
confidence: 99%